Surveying - McCormac, Jack C. (Upper Saddle River, N.J. : Prentice Hall, 1999)
This book is about: Introduction to measurements; INtroduction to distance measurement; Distance correction; Electronic distance measuring instruments; Differential leveling; ...
Keywords: Surveying; Surveying